Accelerating STEM education reform: linked communities of practice promote creation of open educational resources and sustainable professional development - Adam J. Kleinschmit; Anne Rosenwald; Elizabeth F. Ryder; Sam Donovan; Barbara Murdoch; Nealy F. Grandgenett; Mark Pauley; Eric Triplett; William Tapprich; William Morgan (SpringerOpen, 2023)
Abstract The preparation of future scientists, the technical workforce, and informed citizens will require continued transformation to the ways we approach STEM teaching and learning. Undergraduate STEM education is rapidly emerging as a focus of faculty scholarship, but new models for reform need to be developed and tested to accelerate changes in teaching practices. This paper describes a flexible, participant-driven, multi-phase, collaborative approach to developing open educational resources (OERs) that leverages linked communities of practice (CoPs). Equally valuable, our framework for development, adaptation, dissemination, and validation of OERs provides a platform for faculty professional development and sustained support through cooperative mentoring. The three linked CoPs in the framework include incubators for the creation of initial OERs, Faculty Mentoring Networks (FMNs) for the implementation and adaptation of OERs for classroom use, and Education Research Communities to assess the effectiveness of the OERs. The CoPs create numerous benefits for participating faculty, including the ability to collaborate in the Scholarship of Teaching and Learning (SoTL) through scholarly publication of OERs and their assessment; ongoing mentorship in implementation of OERs in the classroom; and development of educational leadership skills and experience. Thus, the three CoPs synergize with one another to build and sustain capacity through providing vetted, up-to-date educational resources, as well as ongoing training and support for faculty. While we developed this approach for the rapidly changing field of bioinformatics, the linked CoP framework will have utility for STEM education reform more broadly and disciplines beyond STEM.